Análise da diversidade e divergência genética em clones de Eucalyptus spp. potencialmente importantes para Goiás - Maciel, Kelly de Jesus Silva (2014)
The success of the Brazilian forestry is due largely to the excellent adaptability of the Eucalyptus genus to our climate and soil conditions. The recent expansion of eucalypts to the North and Midwest regions of Brazil presents challenges such as the need for clones adapted to drought, high temperatures and nutrient deficient soils of Cerrado. Three clonal trials were installed in different regions of Goiás State to evaluate the adaptability and growth of 113 elite clones of Eucalyptus spp. The objective of this study was to estimate the genetic diversity and divergence among 90 of the clones used in three clonal trials installed in different regions of Goiás State. The clones were genotyped with nine microsatellite loci organized into four "multiplex" systems for PCR. The amplified fragments were separated on the ABI–3100 platform (Applied Biosystems). The genotyping was performed using the GeneMapper software (Applied Biosystems). Genetic diversity parameters were estimated using the GDA and Fstat programs. The parameters number of alleles (A), expected heterozygosity (He), observed heterozygosity (Ho), intrapopulation fixation index (f) and allelic richness were estimated for each microsatellite locus. The results showed that all loci used in this study were highly polymorphic, with an average of 16.78 alleles per locus. The EMBRA28 and EMBRA3 loci showed the highest number of alleles (24 and 22). In general, for most markers, the observed heterozygosity had similar estimates when compared to the expected heterozigosity under Hardy-Weinberg Equilibrium. As a result, the fixation index (f) did not differ significantly from zero. Analyses of genetic structure of the clones was performed using the software Structure (version 2.3.4), with K values ranging from 1 to 10, with 10 interactions each. Results indicated presence of three distinct genetic groups (K = 3). However, there was no clear relationship between the populations obtained and the different species of Eucalyptus used in the study. This result can be explained by the clone sample is originated from breeding programs where crosses may have admixed populations, disrupting some genetic structures. Most importantly, the molecular analyses indicate extraordinary genetic diversity within the clonal trials installed in Goiás. This genetic diversity can be exploited for breeding new genetic material adapted to the Cerrado conditions.